Challenges of Religious Moderation in The Context of Radicalism - Akbar Hutagalung, Khairulman (Green Publisher, 2023)
The global dissemination of religious radicalism has evolved into a worldwide issue, prompting intellectuals to engage in discussions and express their concerns. Data for this research were meticulously gathered from reliable sources utilizing a qualitative analytical approach. The focus of the analysis is on countering the escalating trend of radicalism through the lens of religious moderation. The study's findings highlight that a moderate Muslim is characterized by adherence to an acceptable interpretation of Islam. This interpretation incorporates principles of non-violence and moderation, aligned with a belief in democratic and pluralistic approaches, coupled with a spirit of tolerance. This research contributes to the scholarly discourse on the role of literary-based instruction in promoting religious moderation, offering valuable insights for policymakers, educators, and scholars engaged in the global dialogue on countering radicalism and fostering peaceful coexistence.